Does gender equality in sports matter? examining the socio-economic impact on public perceptions - Indelicato, Alessandro (Frontiers in Sports and Active Living, 2025)
IntroductionGender equality (GE) is increasingly becoming a key point on modern political agendas. While governments and civil societies strive to achieve this goal, we may be far from “perfect” equality between women and men. Sport is a good example of some of the inequalities that men and women face, such as pay, discrimination, and unequal opportunities.MethodsThe study uses data from the Special Eurobarometer 525 (April–May 2022) to understand attitudes towards GE in sports (ATGEQS). By applying Fuzzy-Hybrid TOPSIS approach, and other methods like Latent Profile Analysis and Multinomial Logistic Regression, I investigate how gender, age, income, education, political beliefs and nationality affect these attitudes.Results and DiscussionThe Nordic countries have the highest ATGEQS, while support for EU GE policies, left-wing views, and life satisfaction is positively related to favourable attitudes. The findings highlight the need for awareness and policies for sports participation to be created, with greater emphasis on disadvantaged groups.